ANALISIS HUBUNGAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI MENGGUNAKAN REGRESI LINIER BERGANDA - Salwa Regiena Setiawan; Wahyu Widhiarso (Jurnal Industri dan Teknologi Samawa, 2024)
Humans are organizational resources that play an important role in achieving company goals. To achieve organizational goals, of course, there must be a leader who has the ability to influence the motivation of other individuals in the organization. The Surakarta City Cooperatives, SMEs, and Industry Service provides cooperative and micro, small, medium enterprises (MSMEs) and industry services. In July 2023, the Head of Division and Coordinator were replaced, but after the replacement there were several problems in administration and preparation of activities that were classified as large and fatal. This study aims to identify the effect of leadership on employee performance and the relationship between the two variables. The method used is Multiple Linear Regression. Based on the calculations, it shows that employee performance is influenced by decision making (X1), motivation (X2), communication skills (X3), responsibility (X5), and the ability to control emotions (X6). The correlation coefficient (r) of 0.586 shows that the relationship between leadership and employee performance is moderate.